Ethnography and protestant religious discourse: critical discourse analysis of Ministerio Internacional Iglesia Fuente de Agua Viva in Puerto Rico - Borrero, Doris (Boletín de Filología, 2008)
This research is centred on the analysis of the linguistic structures and the persuasive strategies used in religious discourse by the Ministerio Internacional Iglesia Fuente de Agua Viva. Its objective is to identify those mechanisms that legitimate discourse and infl uence the thought and the actions of the audience (van Dijk 1993). The theoretical framework put forward by van Dijk (1993), in his theory about critical analysis of discourse, was used to carry out this research. This theoretical framework states that discourse id is not merely the verbalization of a message, but it includes cognitive aspects such as understanding and reasoning. Besides, theory establishes that discourse effi cacy and power are realized through the use of a social stronghold that in this case would be constituted by religion. The conclusions show which are those linguistic and contextual conditions that back the effectiveness of such religious discourse on the people.